Fatores associados ao conhecimento do Papilomavírus Humano (HPV) entre profissionais da saúde: um estudo de base populacional - Grigolo, Adriane Valentini (2022)
The Human Papillomavirus (HPV) typically infects the skin or the mucous, affecting men and women in various age groups. Although there is a widespread dissemination both in the health care system and in the media about HPV, several studies have shown that health professionals have misconceptions about HPV. Therefore, this research aimed to evaluate the knowledge of health professionals from primary and secondary care levels from the Unified Health System about HPV. This is a cross-sectional, population-based study. The sample consisted of 260 professionals, including physicians, community-health workers (CHW), nurses, nursing technicians and other nursing staff, oral hygiene professionals, dentists, psychologists, endemic agents, and pharmacists in the municipality of Francisco Beltrão, Paraná. A questionnaire was used, measuring socioeconomic and HPV knowledge. Participants’ age ranged from 21 to 66 years, with a mean of 40 years (±9.30 years). The majority of the sample was comprised by women. About 32.8% of the individuals had sufficient knowledge about HPV, while 67.2% had insufficient knowledge. Mann-Whitney tests indicated that professionals who do not have children had higher knowledge about HPV when compared to those with children (p = 0.05). Moreover, lower levels of HPV knowledge were found among CHW compared to other health professionals (p < 0.001). Logistic regression analysis indicated that having children (OR = 0.50; 95%CI: 0.26 - 0.96) and being a CHW (OR = 0.52; 95%CI: 0.28 - 0.97) were independently associated with insufficient knowledge about HPV. In summary, the findings of this study could support strategies to promote both education and health promotion regarding HPV.